Killer stance: An investigation of the relationship between attitudinal resources and psychological traits in the writings of four serial murderers - Hunter, Madison; Grant, Tim (Language and Law / Linguagem e Direito, 2022)
An individual’s set of psychological traits, or their psychopathology, impacts howthey experience theworld around them, and language offers resources that allow for that experience to be shared with and communicated to someone else. That language can then be analyzed for patterns and their connections to the psychological traits. In a forensic context, such connections may give valuable insights. There already exist psychological and linguistic approaches to the analysis of forensic texts, but the psychological approach largely lacks grounding in linguistic theory and the linguistic approach does not typically allow consideration of psychological characteristics. What this paper aims to provide is a step toward bridging that gap. In this paper we examine the system of attitude from the Appraisal framework developed by Martin and White (2005) and adapted by Gales (2010) and Hurt (2020) applying this to the writings of four serial murderers with documented mental health diagnoses. Significant patterns in the attitudinal resources were identified quantitatively and examined qualitatively through the lens of the psychological traits that comprised the authors’ diagnoses to determine if there was a relationship between them. Despite the obvious limitation presented by the sample size, the results of this study suggest the approach presented in this paper warrants further investigation.